2010
DOI: 10.1016/j.jeurceramsoc.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation of SiC under helium with low-pressure oxygen. Part 2: CVD β-SiC

Abstract: In the frame of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…The temperatures of the experiment combined with the atmospheric pressure fall into a regime where SiC is known to actively oxidize. [34][35][36] As a result, SiC particles near the specimen surface underwent active oxidation leaving a surface layer of ∼50 m that was depleted of SiC (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The temperatures of the experiment combined with the atmospheric pressure fall into a regime where SiC is known to actively oxidize. [34][35][36] As a result, SiC particles near the specimen surface underwent active oxidation leaving a surface layer of ∼50 m that was depleted of SiC (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The conclusion of these studies 3,24,58,59 is that in order to withstand high temperatures for prolonged durations that may occur in severe accident scenarios, the SiC/SiC composites must be protected by thicker layers of β-SiC. Substitution of He (with 2 Pa O 2 ) by N 2 (with 0.5 Pa O 2 ) did not cause important differences in oxidation behavior of β-SiC (Fig.…”
Section: Engineered Composites For Use In Nuclear Applicationsmentioning
confidence: 91%
“…Charpentier et al measured oxidation kinetics of sintered α-SiC and CVD β-SiC at oxygen pressures between 0.2 and 100 Pa in He (total pressure 100 kPa) and a broad temperature range. The β−SiC was obtained from Rohm & Haas (USA) and was processed by CVD at 1200-1300 o C. 24 The authors cited above found that the transition between passive and active oxidation regime occurs at higher temperatures for β-SiC than for α-SiC, and the mas loss rate of β-SiC is lower than the one measured for α-SiC on the common temperature range investigated (up to 1800 o C). Figure 2 show theoretical and experimental transitions observed for the two SiC allotropes.…”
Section: Oxidation Of Sic Matrixmentioning
confidence: 99%
See 2 more Smart Citations